Climate policy and inequality in two-dimensional political competition - Waldemar Marz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper examines how income inequality can affect the polarization of heterogeneous party platforms on climate policy (here: carbon tax). The implied consequences for the uncertainty of climate policy can be relevant for risk-averse investors in "green" technologies. Households are heterogeneous with respect to income and preferences for environmentalism and preferred redistribution. A static gametheoretic model of two-dimensional political competition on a carbon tax (with distributional implications) and an income tax is combined with a model of a carbonintensive economy. For a higher inequality of pre-tax income and/or a higher salience of the issue of redistribution, polarization of the parties' carbon tax proposals in the equilibrium can increase - even if the income tax is used to counteract the increase in income inequality. This result does not depend on the progressivity of the carbon-tax revenue recycling mechanism.
Keywords: H23; P16; Q52; Q54; 330; Climate policy; inequality; political economy; multidimensional political competition